A Comparative Study of Number of Children of Educated/ Uneducated Working and Educated/ Uneducated Non-Working Women in Gopalganj Town: A Microeconomic Household Fertility Analysis - Sarker, Bibhuti (IJRDO - Journal of Social Science and Humanities Research, 2017)
The neoclassical microeconomic household theory of fertility reveals that the opportunity cost heavily affects the total cost for a child, in societies where mothers are engaged in work contributing disproportionate share of their time to child rearing. Increasing women’s education, earning opportunities, women’s empowerment lead to lower demand for children. The nature of these existing variables is being changed and new other variables are being introduced with the passage of time and continuing changes in our climate, environment and in the level of economic development. This paper surveys a variety of variables to explore the economic determinants of fertility and then summarizes the empirical findings that seek to explain mostly cross-sectional differences in individual/ family data in Gopalganj town. Differences between obtained data at one point in time are also shown to be consistent with the microeconomic approach to fertility with some trivial exception; some new other emerging variables – less significant but important – are found to affect the demand for children.